The daytime feeding frequency affects appetite-regulating hormones, amino acids, physical activity, and respiratory quotient, but not energy expenditure, in adult cats fed regimens for 21 days - Camara, Alexandra; Verbrugghe, Adronie; Cargo-Froom, Cara; Hogan, Kylie; DeVries, Trevor J.; Sanchez, Andrea; Robinson, Lindsay E.; Shoveller, Anna K. (PLOS ONE, 2020)
The effects of feeding frequency on postprandial response of circulating appetite-regulating hormones, insulin, glucose and amino acids, and on physical activity, energy expenditure, and respiratory quotient were studied in healthy adult cats. Two experiments were designed as a 2 x 3 replicated incomplete Latin square design. Eight cats, with an average body weight (BW) of 4.34 kg ± 0.04 and body condition score (BCS) of 5.4 ± 1.4 (9 point scale), were fed isocaloric amounts of a commercial adult maintenance canned cat food either once (0800 h) or four times daily (0800 h, 1130 h, 1500 h, 1830 h). Study 1 consisted of three 21-d periods. On day 14, two fasted and 11 postprandial blood samples were collected over 24 hours to measure plasma concentrations of ghrelin, GLP-1, GIP, leptin, PYY, insulin and amino acids, and whole blood glucose. Physical activity was monitored from day 15 to 21 of each period. In Study 2 indirect calorimetry was performed on the last day of each period. Body weight was measured weekly and feed intake recorded daily in both experiments. No effect of feeding regimen on BW was detected. Cats eating four times daily had lesser plasma concentrations of GIP and GLP-1 (P<0.05) and tended to have lesser plasma PYY concentrations (P<0.1). Plasma leptin and whole blood glucose concentrations did not differ between regimens (P>0.1). Cats fed once daily had a greater postprandial plasma amino acid response, and greater plasma ghrelin and insulin concentrations (P<0.05). Physical activity was greater in cats fed four times (P<0.05), though energy expenditure was similar between treatments at fasting and in postprandial phases. Finally, cats eating one meal had a lower fasting respiratory quotient (P<0.05). Overall, these data indicate that feeding once a day may be a beneficial feeding management strategy for indoor cats to promote satiation and lean body mass.